2000
DOI: 10.1128/aem.66.1.170-175.2000
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Activation during Oxidation of Methoxyhydroquinones by Laccase from Pleurotus eryngii

Abstract: Oxygen activation during oxidation of the lignin-derived hydroquinones 2-methoxy-1,4-benzohydroquinone (MBQH 2 ) and 2,6-dimethoxy-1,4-benzohydroquinone (DBQH 2 ) by laccase from Pleurotus eryngii was examined. Laccase oxidized DBQH 2 more efficiently than it oxidized MBQH 2 ; both the affinity and maximal velocity of oxidation were higher for DBQH 2 than for MBQH 2 . Autoxidation of the semiquinones produced by laccase led to the activation of oxygen, producing superoxide anion radicals (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 48 publications
5
62
0
3
Order By: Relevance
“…Further support for this hypothesis is that white rot fungi, which do not utilize the hydroxyl radical as the major oxidant (30,32), also produce oxalate (39,40,42,49). Despite reports on how the hydroxyl radical may be formed in white rot fungi (4,17,18), it is unlikely that oxalate would have a role in its formation. The chemical signatures of wood affected by white rot fungi and brown rot fungi are different (30).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Further support for this hypothesis is that white rot fungi, which do not utilize the hydroxyl radical as the major oxidant (30,32), also produce oxalate (39,40,42,49). Despite reports on how the hydroxyl radical may be formed in white rot fungi (4,17,18), it is unlikely that oxalate would have a role in its formation. The chemical signatures of wood affected by white rot fungi and brown rot fungi are different (30).…”
Section: Discussionmentioning
confidence: 85%
“…The quinone undergoes cyclic oxidation-reduction reactions, serving as a shuttle for electrons from intracellular donors to extracellular acceptors. Although a similar mechanism has been proposed for white rot fungi (4,17,18) for hydroxyl radical formation, product analysis suggests that hydroxyl radical oxidation is relatively minor in comparison to peroxidase oxidation (30,32). The role of oxalate, ubiquitously found in brown rot fungi, as a chelating agent, and the role of pH, which is altered by the fungus, are not clear.…”
mentioning
confidence: 93%
“…G. trabeum then reduces these quinones to regenerate the hydroquinone and catechol that are needed to produce additional Fenton reagent. A similar redox cycle may contribute to biodegradation by some white-rot fungi (9).…”
mentioning
confidence: 99%
“…Biological degradation of sludge and wheat straw is a complex process affected by many factors, and analysis of optimum growth conditions for obtaining the maximum amount of fermentable sugars is the first step to understand the mechanisms of fungal degradation (Guillén et al 2000;Wan and Li 2010). The results obtained clearly showed that the fungus G. lucidum is capable of producing lignocellulolytic enzymes during growth in primary sludge mixed with wheat straw.…”
Section: Resultsmentioning
confidence: 72%